Determination of the calorific value of the forest species Cupressus sp. (Ciprés) (GnosisWisdom, 2024)
Objective: To characterize the clinical epidemiological profile of nutritional deficiency in groups of greater susceptibility in a quintile V region of poverty in Peru.  Methods: The study is of a retrospective cross-sectional observational type; data were collected on the characteristics of the clinical and epidemiological profile of nutritional deficiencies in the most vulnerable groups.  Results: There is a significant decrease in moderate anemia in pregnant women; from 24.8% in 2015 to 13.0% in 2019, of mild anemia; from 20.9% to 15.6% (pvalue = .000), in children; moderate anemia from 19.4% to 11.3%, but in mild anemia from 21.3% to 20.2% (pvalue = .000); there is a significant increase in overweight in pregnant women; from 26.3% to 30.7%, but a decrease in the nutritional deficit assessment, from 10.6% to 8.4% (pvalue = .000); stability of acute malnutrition in children under 5 years of age; from 1.2% (2015) to 1.1% (2019), likewise a stationary aspect of the eutrophic nutritional level from 93.3% to 93.5%; but there is a slight increase in overweight; from 3.75 to 4.4% for 2019; slight reduction in chronic malnutrition in children under 5 years of age; from 31.6% (2015) to 29.5% (2019), likewise a stationary aspect of the eutrophic nutritional level from 68.0% to 70.4%; slight reduction in global malnutrition in children under 5 years of age; from 7.1% (2015) to 5.1% (2019), likewise a stationary aspect of the eutrophic nutritional level from 92.8% to 94.9% for 2019. Conclusion: The nutritional deficiency of anemia still persists and malnutrition in pregnant women and children considered a public health problem.
Keywords: Calorific value; Cupressus sp; Bomb calorimeter; Physical properties; Biofuels